2023
DOI: 10.3390/su15129270
|View full text |Cite
|
Sign up to set email alerts
|

Power of eWOM and Its Antecedents in Driving Customers’ Intention to Revisit: An Empirical Investigation on Five-Star Eco-Friendly Hotels in Saudi Arabia

Abstract: In recent years, electronic word-of-mouth (eWOM) has greatly impacted the hotel industry, as social media and online review platforms have given customers many opportunities to share their personal experiences with other individuals. Hence, this study aimed to empirically investigate several relationships within the setting of five-star eco-friendly hotels in Saudi Arabia. These included: (1) the direct impact of perceived quality (PQ), positive emotional experience (PEE), and customer satisfaction (CS) on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…In addition, some scholars have found that the landscape, nightscape, and walkway of an urban waterfront influence people's satisfaction with the space [40]. Therefore, the qualities of destination attributes determine tourist satisfaction as well as future revisit intentions, WOM promotion [28,66,67], service experience, and loyalty (e.g., [61]). In competitive markets, destination attributes play a key role in maintaining competitive advantage [16] and have a meaningful impact on forming a destination's image [55].…”
Section: Destination Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some scholars have found that the landscape, nightscape, and walkway of an urban waterfront influence people's satisfaction with the space [40]. Therefore, the qualities of destination attributes determine tourist satisfaction as well as future revisit intentions, WOM promotion [28,66,67], service experience, and loyalty (e.g., [61]). In competitive markets, destination attributes play a key role in maintaining competitive advantage [16] and have a meaningful impact on forming a destination's image [55].…”
Section: Destination Attributesmentioning
confidence: 99%
“…Scholars have claimed that reviews on these websites represent a more general and widespread form of WOM, namely electronic WOM (eWOM) [24,25], and that the ratings represent customers' or tourists' overall satisfaction with the quality, service, or experience of a product or destination [26,27]. For sustainable destination development, eWOM might be more cost-effective [24,28] and influential [29,30] than other sources of information because of the intangible nature of tourism services [31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Park and Kang [38] found that customers' green perceptions and their feelings toward eco-friendly artwork influence their intention to visit eco-friendly hotels. Noticeably, the majority of previous studies have mainly focused on foreign visitors or both local and foreign visitors [39,40]. Table 1 below provides an overview of several pertinent prior studies falling within the scope of this study.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%